Morphology and enhanced star formation in a Cartwheel-like ring galaxy. Issue 1 (12th September 2017) - Renaud, F.; Athanassoula, E.; Amram, P.; Bosma, A.; Bournaud, F.; Duc, P.-A.; Epinat, B.; Fensch, J.; Kraljic, K.; Perret, V.; Struck, C.
Abstract: We use hydrodynamical simulations of a Cartwheel-like ring galaxy, modelled as a nearly head-on collision of a small companion with a larger disc galaxy, to probe the evolution of the gaseous structures and flows, and to explore the physical conditions setting the star formation activity. Star formation is first quenched by tides as the companion approaches, before being enhanced shortly after the collision. The ring ploughs the disc material as it radially extends, and almost simultaneously depletes its stellar and gaseous reservoir into the central region, through the spokes, and finally dissolve 200 Myr after the collision. Most of star formation first occurs in the ring before this activity is transferred to the spokes and then the nucleus. We thus propose that the location of star formation traces the dynamical stage of ring galaxies, and could help constrain their star formation histories. The ring hosts tidal compression associated with strong turbulence. This compression yields an azimuthal asymmetry, with maxima reached in the side furthest away from the nucleus, which matches the star formation activity distribution in our models and in observed ring systems. The interaction triggers the formation of star clusters significantly more massive than before the collision, but less numerous than in more classical galaxy interactions. The peculiar geometry of Cartwheel-like objects thus yields a star (cluster) formation activity comparable to other interacting objects, but with notable second order differences in the nature of turbulence, the enhancement of the star formation rate, and the number of massive clusters formed.